The Impact of Entrepreneurial Characteristics on Entrepreneurial Intention of Sudanese and Omani University Students - Tariq Mohamed Salih Atiya; Zaroug Osman Bilal; Mohamed Abulhamid; Siddig Abdelrahman Shoaib (European Scientific Journal, ESJ, 2019)
This study aims to identify the level of availability of entrepreneurial characteristics among undergraduate students in some universities of Sudan and Oman, and test whether these characteristics have a significant impact on the entrepreneurial intention of these students. The study also intends to make comparison between the attitudes of students in Sudan and Oman towards establishing their businesses (self-employment). The sample of the study (n = 574) consists of students from University of Bahri, Sudan International University, and Dhofar University. In order to achieve these objectives, the study adopted the descriptive and analytical approach and used the questionnaire as a tool for collecting primary. The findings reveal that, there is a statistically significant impact of the entrepreneurial characteristics among undergraduate students (need for achievement, self-efficacy and locus of control) on their entrepreneurial intention. The study also found that there are statistically significant differences in the views of the respondents according their universities, concerning the locus of control and entrepreneurial intention. The analysis showed that locus of control among students of Dhofar University and Sudan International University was higher than that of University of Bahri students. Furthermore, it was found that the entrepreneurial intention among students of Dhofar University was higher than that of Sudan International University & University of Bahri students